การเปลี่ยนแปลงของตัวแปรทางชีวกลศาสตร์ของการว่ายน้ำ 200 เมตร ท่าฟรอนท์ ครอลในรยางค์ส่วนบนของนักกีฬาว่ายน้ำทีมชาติไทย - อัครยา ศีลสังวรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
The purpose of the research was to compare the changes in biomechanical upper extremities variables of 200-meter front crawl swimming in Thai nation swimmers.Seven male front crawl Thai Nation swimmers who participated in the 29th Sea Game in Malaysia were recruited by purposive sampling.  Biomechanical variables were analyzed using 16 hi-cameras installed on land and in water in the swimming flume at Faculty of Sports Science, Chulalongkorn University. All participants wore a marker-embedded swimming suit to swim in a time-equivalent duration at 75% of front crawl speed measured in a swimming pool. Joint angles and velocities were measured in 5 distances, which were 15-35 m., 65-85 m., 115-135 m., 165-185 m., and 196-200 m. The joint angles and velocities were tested with a One-way ANOVA at .05 level of significance.The results showed that the average joint angles and joint velocities were statistically significant different among 5 distances.  The trajectories of joint angles and joint velocities were modelled using a Simple Harmonic Equation. The predicted trajectories of joint angles and velocities were 80% accurate. The equation showed that the different distances resulted in different cycle times of joint angles and velocities.In conclusion, swimming in different laps resulted in different average joint angles and velocities of the upper limb. The movement pattern of upper limb joints was similar among different laps, but the duration to complete one cycle of each joint increased as the swimming distance increased.